Fecal Microbiota Transplantation Activity of Floccularia luteovirens Polysaccharides and Their Protective Effect on Cyclophosphamide-Induced Immunosuppression and Intestinal Injury in Mice - He Ma; Abdul Mueed; Yanxu Ma; Muhammad Ibrahim; Ling Su; Qi Wang (Foods)
Floccularia luteovirens polysaccharides (FLP1s) have potential biological activities. Our previous study showed that FLP1s positively regulated gut immunity and microbiota. However, it is still unclear whether FLP1s mediate gut microbiota in immunosuppressed mice. This research aims to explore the relationship between FLP1-mediated gut microbes and intestinal immunity in immunosuppressed mice through fecal microbiota transplantation (FMT). The results demonstrated that FLP1s exhibited prebiotic and anti-immunosuppressive effects on CTX-induced immunosuppressed mice. FFLP1 treatment (microbiota transplantation from the fecal sample) remarkably elevated the production of sIgA and secretion of the anti-inflammatory cytokines IL-4, TNF-α, and IFN-γ in the intestine of CTX-treated mice, inducing activation of the MAPK pathway. Moreover, FFLP1s mitigated oxidative stress by activating the Nrf2/Keap1 signaling pathway and strengthened the intestinal barrier function by upregulating the expression level of tight junction proteins (occludin, claudin-1, MUC-2, and ZO-1). Furthermore, FFPL1s restored gut dysbiosis in CTX-treated immunosuppressed mice by increasing the abundance of Alloprevotella, Lachnospiraceae, and Bacteroides. They also modified the composition of fecal metabolites, leading to enhanced regulation of lipolysis in adipocytes, the cGMP-PKG pathway, the Rap1 signaling pathway, and ovarian steroidogenesis, as indicated by KEGG pathway analysis. These findings indicate that FLP1s could modulate the response of the intestinal immune system through regulation of the gut microbiota, thus promoting immune activation in CTX-treated immunosuppressed mice. FLP1s can serve as a natural protective agent against CTX-induced immune injury.